A atuação dos bombeiros na Guerra dos Farrapos (1835-1845): agentes de informação e redes de espionagem - Giordani, Santa Giovana Mendes (2020)
The present research intend to treat the activities developed by the agents of information during the War of Farrapos in the period of 1835-1845. Thereby the space of study will be the Rio Grande de São Pedro province, created in February 28, 1821. These agents of information are denominated as espias, bombeiros e vaqueanos. During the war, they operated in an espionage network that last by all the conflict. By the almost then years of war, the two opposite’s sides displaced this network of agents by the main spots of the province. The rebels has been the first to assemble the espionage network on the purpose to move in the open field. By the time, the imperials pass to work with this war strategy. The informants act in satellite strategically placed locations. They are delegated to inform the officials and commanders to the military preparations being developed in the province. These agents inform the exactly positions of the enemy forces, their military preparations, besides, when possible their future moves. Infiltrating, sometimes, in the enemy army corps and their information’s are helpful the offensive and defensive previsions, launching recon and observation patrols. In this way, the agents of information had a significant role in the military strategies to both farrapos and imperials. We should consider that in war times the espionage network increase and with that the confidentiality of the activities developed by the agents of information. Therefore, we deal with the classified nature of this activity being essential to establish the relations of reciprocity and confidence between commanders and commandeers. These relations found in the province express the hierarchy and the relations of power in the southern society. In general, the functions of the spies was the gather and transfer of information, information which has to arrive modestly and reliably to the superior authorities the ones we intend to trace.